Verify the following. a x (b + c) = (a x b) + (a x c) if a = 18, b = 7 and c = -3​

Question

Verify the following.

a x (b + c) = (a x b) + (a x c) if a = 18, b = 7 and c = -3​

in progress 0
Audrey 4 weeks 2021-08-14T04:16:41+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-14T04:18:15+00:00

    Answer:

    a = 18, b = 7 and c = -3

    a x (b + c) = (a x b) + (a x c)

    18×{7+(-3)} = (18×7)+{18×(-3)}

    18×4=126+(-54)

    72=72

    Verified

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )